PENGARUH OVERHEATING TERHADAP TERJADINYA DISTORSI DAN HASIL RT PADA PENGELASAN GTAW UNTUK MATERIAL SOLID INCONEL UNS N06625 - Aran, Mikhael Milang; Susilo, Trisno; Hilmy, Zakwan (UNIMAR AMNI Semarang, 2024)
WPS has several parameters that determine heat input. This research was conducted to determine the welding results when the heat input used exceeds the value specified in the WPS used in the field. The research was carried out on 3 samples that have the same dimensions, namely 2